Pengaruh Pemberian Edukasi Terhadap Pengetahuan Complementery Alternative Medicine (CAM) Pada Penderita HIV di Jambi - JELLY PERMATASARI; INDRI MEIRISTA; NADIATUL MAWADDAH (HANG TUAH MEDICAL JOURNAL, 2020)
ABSTRACT Background : HIV / AIDS is a public health problem that needs serious attention from the government. Besides to conventional medicine people with HIV / AIDS often use complementary and alternative medicines (CAM) in order to increase the qualityhealth. Complementary and alternative medicine (CAM) uses natural ingredients, not only restricted to herbal plants, but also includes the use of other natural vitamins and minerals. Compared to conventional treatments, CAM therapy is more save to use because it does not cause serious side effects. The purpose of this study was to know what are the effects of providing CAM education to ODHA at the Jambi Kanti Sehati Sejati Foundation. Method:This research was a quasi-experimental one type pretest-posttest type of research and is a type of quantitative descriptive study with prospective data collection. There were 35 ODHA who were respondents in this study and registered as members of the Jambi Kanti Sehati Sejati Foundation. Results: on demographic characteristics and CAM knowledge were obtained from questionnaires that given before and after giving the education, and proved by paired T test so that significance values ≤ 0.05 were obtained. Conclusion :there is the influence of education on CAM knowledge in HIV suffererof